Structural Designs and Mechanogating Mechanisms of the Mechanosensitive Piezo Channels. Issue 6 (June 2021) - Jiang, Yan; Yang, Xuzhong; Jiang, Jinghui; Xiao, Bailong
Abstract : The evolutionarily conserved Piezo channel family, including Piezo1 and Piezo2 in mammals, serves as versatile mechanotransducers in various cell types and consequently governs fundamental pathophysiological processes ranging from vascular development to the sense of gentle touch and tactile pain. Piezo1/2 possess a unique 38-transmembrane (TM) helix topology and form a homotrimeric propeller-shaped structure comprising a central ion-conducting pore and three peripheral mechanosensing blades. The unusually curved TM region of the three blades shapes a signature nano-bowl configuration with potential to generate large in-plane membrane area expansion, which might confer exquisite mechanosensitivity to Piezo channels. Here, we review the current understanding of Piezo channels with a particular focus on their unique structural designs and elegant mechanogating mechanisms. Highlights: Mechanotransduction by ion channels converts mechanical forces into biological signals. Piezo1 is a versatile mechanotransduction channel for initiating Ca 2+ signaling in various non-excitable cell types, and Piezo2 mainly functions in sensory neurons and specialized cell types such as Merkel cells for sensing touch, tactile pain, balance, breath, blood pressure, and bladder fullness. Piezo1/2 form a three-bladed, propeller-like homotrimeric structure with the signature nano-bowl configuration of the highly curved TM region consisting of a total of 114 TM helices. Recent studies show that Piezo channels might utilize a dual-gating mechanism, in which the TM gate might be regulated by the top cap, while the lateral plug gates are controlled by the blade beam via an elegant plug-and-latch mechanism. Emerging models, including force-from-lipids and force-from-filament models, show how Piezo channels may respond to local changes of membrane curvature and tension and long-range mechanical perturbation across a cell.